2022
DOI: 10.3389/froh.2022.904711
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oral Microbiota on the Presence of IgA Anti-Citrullinated Protein Antibodies in Gingival Crevicular Fluid

Abstract: IntroductionThe relation between rheumatoid arthritis (RA) and periodontitis (PD) has been investigated ever since the discovery of the citrullinating enzyme peptidyl arginine deaminase presents in the oral bacterium Porphyromonas gingivalis. Recently, we demonstrated the presence of RA autoantibodies, especially of IgA anti-citrullinated protein antibody (ACPA), in gingival crevicular fluid (GCF) of Indonesian patients with and without RA or PD which might indicate the local formation of RA antibodies in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Additionally, as the contributing factors of periodontal disease in SSc are generally yet unknown, it may be possible that inflammatory processes may be more relevant for periodontal disease in lcSSc than alterations of endothelial dysfunction, as some studies reported changes of different cytokines correlating to periodontal disease in SSc patients 42,46 . Further mechanisms, which were yet investigated to the best of our knowledge only in other autoimmune diseases than in SSc, may also contribute to periodontal disease in SSc, including the presence of gingival autoantibodies, dysbalance of T cells or Fcμ receptor polymorphism, and need to be investigated by further studies 47–49 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as the contributing factors of periodontal disease in SSc are generally yet unknown, it may be possible that inflammatory processes may be more relevant for periodontal disease in lcSSc than alterations of endothelial dysfunction, as some studies reported changes of different cytokines correlating to periodontal disease in SSc patients 42,46 . Further mechanisms, which were yet investigated to the best of our knowledge only in other autoimmune diseases than in SSc, may also contribute to periodontal disease in SSc, including the presence of gingival autoantibodies, dysbalance of T cells or Fcμ receptor polymorphism, and need to be investigated by further studies 47–49 …”
Section: Discussionmentioning
confidence: 99%
“…42,46 Further mechanisms, which were yet investigated to the best of our knowledge only in other autoimmune diseases than in SSc, may also contribute to periodontal disease in SSc, including the presence of gingival autoantibodies, dysbalance of T cells or Fcμ receptor polymorphism, and need to be investigated by further studies. [47][48][49] Significant correlations were found between parameters of periodontal disease and EUSTAR index as well as UCLA SCTC GIT 2.0 total score. EUSTAR index may be used as a tool for disease activity in SSc, while UCLA SCTC GIT 2.0 questionnaire may be an indicator of gastrointestinal involvement in SSc.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 93%